An illustrated key to the soldiers of Cyranotermes Araujo with a new species from Amazonia (Isoptera: Termitidae: Nasutitermitinae) - Rocha, Mauricio M.; Carrijo, Tiago F.; Cancello, Eliana M. (Zootaxa, 2012)
Until now, the Neotropical termite genus Cyranotermes was known from three species: C. timuassu Araujo, C. glaber Constantino, and C. caete Cancello. In this paper a new species, Cyranotermes karipuna, n. sp., is described and illustrated from imago, worker, and soldier castes, along with its nest. It is also provided an illustrated identification key to species of Cyranotermes, a map with the occurrence of all species, and the first description of the imago caste of Cyranotermes, based on the first description of the imago of C. timuassu, and the imago of the new species.